Amniotic fluid l-ergothioneine concentrations in pregnant sheep after natural mating and transfer of vitrified/thawed in-vitro produced embryos. (October 2015) - Sotgia, Salvatore; Zinellu, Angelo; Arru, Dionigia; Nieddu, Stefano; Strina, Alessandro; Ariu, Federica; Pintus, Gianfranco; Carru, Ciriaco; Bogliolo, Luisa; Ledda, Sergio
Abstract: l -ergothioneine levels were measured in amniotic fluid of pregnant sheep after natural mating and transfer of vitrified/thawed in-vitro produced embryos. Amniotic fluids were collected between 60 and 65 and 80–85 days of gestation and analysed by an ultra-performance liquid chromatographic (UPLC) method with fluorescence detection. l -Ergothioneine concentrations ranged between 0.23 and 9.36 μmol/L and were significantly higher in pregnancy obtained by the transfer of vitrified/thawed in-vitro produced embryos. Conversely, no significant changes in amniotic fluid l -ergothioneine concentrations were observed according to the stages of pregnancy considered in this study. These findings suggest that l -ergothioneine concentrations, are not affected as much by the gestational age, but rather by the method used to induce the pregnancy. On the whole, the measurement of l -ergothioneine in amniotic fluid could serve as a useful biomarker of oxidative stress and/or inflammatory state in pregnancy. Highlights: l -Ergothioneine was detected and measured in amniotic fluid of pregnant sheep. l -Ergothioneine was measurable both after natural mating and by transfer of vitrified/thawed in-vitro produced embryos. l -Ergothioneine levels showed a non-significant trend to decrease according to the days of gestation. l -Ergothioneine levels were significantly higher in pregnancies induced by transfer of vitrified/thawed in-vitro produced embryos.